"O negro do Pomba quando sai da Rua Nova, ele traz na cinta uma cobra coral": os desenhos dos corpos-territórios evidenciados pelo Afoxé Pomba de Malê - Miranda, Eduardo Oliveira (2014)
This work aims to analyze the graph-visual elements outlined by bodies-territories Afoxé Pomba de Malê, with emphasis on parades during Micareta of Feira de Santana, Bahia. To do this, have made every effort to answer the following problem: How does the design of the bodies-territories evidenced by Afoxé Pomba de Malê? In this scenario, we resorted to the Design, Planning and Territory Body-category associated with methodological crossroads between the Hermeneutics of Visuality with Oral History. Weaving the historical trajectory of Afoxé Pomba de Malê entailed analyzing the constitution of New Street, city originally occupied by black populations derived from Reconcavo Baiano, under the permission of Mrs. Pomba, who held possession of the land district. The participation of blacks in that area provided an opportunity to ritualize the African Legacy, identified during this research as one of the factors responsible for the founding of Afoxé in vogue. In the quest for understanding of the visual elements scrawled by bodies-found territories of pombalenses to setup Projetual design, with leads in design-to-artifact and design-for-communication. Desenhísticos such aspects, they provide the dimensions outlined in the Quilombo territorialities Area as well as the appropriation of the public space of the larger party Feirense street. Develop this work with looks of Geography becomes an embryonic action, since the category of analysis-Body Territory, until the ending of this thesis, has received contributions from other geographers. Thus, I see this as an important starting point in provocative tessitura as well as collaboratively to Cultural Geography. Moreover, African ancestry brought valuable in terms of the perception of immaterial energy potential motivators contributions, which, at various times, were found in the surveyed areas.